Analysis of Potential Coastal Resources for Recommendations for Designating Marine Protected Areas in Kondang Merak Bay, Malang Regency - Dimas Syarif Alim; Dhira K Saputra; Arief Darmawan; Kiki Rizky Arisandy; Anthon Andrimida (Jurnal Biologi Tropis, 2023)
Kondang Merak has allocated as MPA Site based on East Java Province Government Decree No. 1/2018 on the Zoning Plan for Coastal and Small Islands Areas Provinsi Jawa Timur Years 2018-2038. To this date, Kondang Merak Beach’s lack of zoning and management plan. This research conducted to asses coastal area resources on Kondang Merak Beach and to recommend MPA category. This research is done by doing a survey on identifying coastal habitat and protected species, scoring and drafting zoning plan based on conservation features and resource use which has been recorded. On the other hand, Forum Group Discussion with locals stakeholder were carried out to ensure the preference of the proposed zoning. The result showed that Kondang Merak Beach has 0,15 Ha of mangrove ecosystem, 0,23 Ha of seagrass ecosystem, 39,7 Ha of coral reef ecosystem, and 2 Ha of fish apartment site. The zoning map shows that there are two high potential site as core zone, covering both area of 12,4 Ha and 6,5 Ha.